Role of GRPR in Acupuncture Intervention in the "Itch-scratch Vicious Cycle" Spinal Circuit of Chronic Pruritus - Jia-jia Liu; Xuemei Li; Jing Guo; Shuguang Yu; Sha Yang (BMC, 2023)
Abstract Many previous studies have shown the potential antipruritic effect of acupuncture. This paper reviews the antipruritic mechanisms of acupuncture according to these aspects: sample characteristics, detail of intervention, and effects evaluation. The majority of research on acupuncture's antipruritic effect has focused on primary afferents of the peripheral mechanism. Relatively few studies, however, have addressed the central mechanisms. Combination the latest research achievements of chronic itch, gastrin-releasing peptide receptor (GRPR) in the dorsal horn of the spinal cord may represent the first molecule identified that is dedicated to mediating the itch response and may provide an important therapeutic target for the treatment of chronic pruritic conditions. Therefore, GRPR may be a new target for acupuncture to relieve itch in the future and provide new ideas for acupuncture intervention in the mechanisms of the spinal level of the "itch-scratch vicious cycle" of chronic itch.